Impact of Green Banking, Sustainability Report, and Enterprise Risk Management on Financial Performance - Kuncoro, Dyas Aji; Haryati, Tantina (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study analyzes the impact of Green Banking (GB), Sustainability Report (SR), and Enterprise Risk Management (ERM) on financial performance, proxied by Return on Assets (ROA). It aims to confirm the influence of these variables, reconcile inconsistent prior findings, and explain profitability fluctuations within Indonesia's banking sector. Methodology: Focusing on conventional commercial banks listed in the Inisiatif Keuangan Berkelanjutan Indonesia (IKBI) from 2019 to 2023, secondary data (annual and sustainability reports) were obtained from company websites. A purposive sample comprising 50 observational units was selected. Data analysis employed the Structural Equation Model-Partial Least Square (SEM-PLS) method with SmartPLS 4 software.. Results: GB and SR disclosure does not significantly affect financial performance. ERM disclosure, conversely, significantly and positively influences it.. Findings: This suggests short-term sustainability practices are not fully reflected in financial outcomes. ERM's positive impact highlights its role in corporate financial stability. Novelty: This research uniquely contributes by addressing prior inconsistencies and elucidating profitability variations within Indonesia's banking sector. Originality: It offers a comprehensive analysis of Green Banking, Sustainability Report, and Enterprise Risk Management in the specific context of IKBI-listed banks, providing new perspectives on their financial impact. Conclusion: GB and SR disclosure shows no significant short-term financial impact. ERM is a positive and significant determinant of financial performance in Indonesian conventional commercial banks. Type of Paper: Empirical Research paper